2012
DOI: 10.1016/j.virusres.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus distribution in tissues and molecular characterization of strains from naturally infected non-hematophagous bats

Abstract: Bats are main reservoirs for Lyssavirus worldwide, which is an important public health issue because it constitutes one of the big challenges in rabies control. Yet, little is known about how the virus is maintained among bats, and the epidemiological relationships remain poorly understood. The aim of the present study was to investigate the distribution of the rabies virus (RABV) in bat tissues and organs and to genetically characterize virus isolates from naturally infected non-hematophagous bats. The hemine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…Prevalence is much higher in sick bats, with estimates ranging from 10% to 92% of grounded Tadarida brasiliensis (Constantine, 1993;Davis et al, 2012). A high seroprevalence rate has been detected in apparently healthy bats, suggesting that they may be able to survive infection (Allendorf et al, 2012). Bats typically undergo a 2-25 week incubation period, although prolonged incubation of over 1 year has been reported (Brass, 1994).…”
Section: Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence is much higher in sick bats, with estimates ranging from 10% to 92% of grounded Tadarida brasiliensis (Constantine, 1993;Davis et al, 2012). A high seroprevalence rate has been detected in apparently healthy bats, suggesting that they may be able to survive infection (Allendorf et al, 2012). Bats typically undergo a 2-25 week incubation period, although prolonged incubation of over 1 year has been reported (Brass, 1994).…”
Section: Rna Virusesmentioning
confidence: 99%
“…In one study of bats infected with Australian bat lyssavirus, the highest frequency and severity of microscopic lesions was detected in the hippocampus, thalamus and midbrain, and medulla oblongata and pons (Hooper et al, 1999). Lyssaviral antigen has been detected in bats in the central and peripheral nervous system as well as in other tissues; reported affected sites include brainstem, cerebellar Purkinje cells, hippocampus, cerebrum, thalamus and midbrain, peripheral autonomic ganglia, nerve plexuses of the gastrointestinal tract, intramuscular nervous tissue, adrenal medulla, salivary gland, tongue, brown fat, lung, heart, kidney, bladder, stomach, intestine, and feces (Allendorf et al, 2012;Davis et al, 2013;de Araújo et al, 2014;Hooper et al, 1999;Schatz et al, 2014;Stein et al, 2010).…”
Section: Rna Virusesmentioning
confidence: 99%
“…Resistance to vancomycin among enterococci has emerged as a general problem and is now found in patients with FN [25]. We found that 5 % of BSIs were due to Enterococcus spp., and 50 % were VRE.…”
Section: Discussionmentioning
confidence: 73%
“…Given these features and the recognized status of bats as reservoirs for RABVs in the Americas, individual bats may experience repeated exposure to RABV during their lifetime 22 . Hematophagous, frugivorous, and insectivorous bats can transmit http://dx.doi.org/10.21615/cesmvz.12.2.5 the RABV 23 , and phylogenetic analysis using nucleotide sequences of N or G genes revealed that RABV is grouped into clusters according to the bat species that support the existence of species-specific variants or lineages of the virus 19,24 .…”
Section: Rabies Virus Transmissionmentioning
confidence: 99%
“…The virus was detected in tongue (92 % and 85 %), brown fat (82 % and 77 %), lung (62 % and 77 %), heart (42 % and 77%), stomach (92 % and 64 %), liver (38 % and 67 %), spleen (43 % and 27 %), bladder (73 % and 88 %), kidney (77 % and 38 %), intestine tissues (77 % and 38 %), and feces (38 % and 42 %) from frugivorous and insectivorous bats. It was noted that the virus was higher in stomachs of frugivorous bats than from insectivorous bats 19 . A possible reason for those findings could be that infected bats defecate on the fruits that are eaten later by frugivorous bats, which ingest the virus.…”
Section: Pathogenesis Of Rabiesmentioning
confidence: 99%